An idea man (the life of Otto Herbert Schmitt). - Harkness, J.M.
This work recounts the life of Otto Herbert Schmitt who is most widely known as the inventor of the Schmitt trigger, which he developed as a graduate student in the mid-1930s. Schmitt remained an active scientist, engineer, and intellectual until the mid-1990s - six decades that brimmed with energy, effort, and insights. Viewing his life in full context suggests that the Schmitt trigger was a mere prelude to his greatest innovation, which Schmitt fully articulated near the end of his career: the concept of a biomimetic approach to science and engineering - an idea rather than a gadget. Schmitt played instrumental roles in establishing a number of the professional associations that continue to provide vital means of interchange among biophysicists and biomedical engineers.
Keywords: Schmitt trigger; Biomedical engineering; Biomimetics; Biophysics